STRUGGLE FOR TRUTH OF DASTAN'S LIFE REFLECTED IN MIKE NEWELL'S PRINCE OF PERSIA MOVIE (2010): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SUPRIYANTO, SUPRIYANTO (2011)
This study is proposed to reveal how the struggle for truth of Dastan's life reflected in Prince of Persia directed by Mike Newell which is published in 2010. The object of the study is the Prince of Persia movie directed by Mike Newell. The objectives of the study are to analyze the structural elements in the movie and to analyze the Struggle for truth based on an Individual psychological approach. The writer employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of Prince of Persia and the secondary data source is information related to the primary data source, website, and book on individual psychological approach. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis, Mike Newell wants to deliver a message that truth can defeat anything and it is the master key to open the gates of happiness. Second, based on the Individual psychological analysis, Mike Newell wants to reflect that the struggle for truth is being represented by Dastan's life.